The lice of the Tristan da Cunha Archipelago (Insecta: Phthiraptera). - Hänel, Christine; Palma, Ricardo L. (Contributions to Entomology = Beiträge zur Entomologie, 2007)
All the louse species reported in the literature from the Tristan da Cunha archipelago have been compiled, listed and discussed, including five additional species records based on material recently collected or identified in previous collections. A total of 54 louse species (including 6 records identified at the generic or subgeneric level only), belonging to 21 genera, have been listed together with their hosts: 20 bird species and one mammal. A brief discussion on the history of louse collections made on and around the archipelago, and detailed louse records from the four main islands are also given. Keywords Phthiraptera, Tristan da Cunha, Nightingale, Inaccessible, Gough, South Atlantic Ocean, seabirds, landbirds.